2011
DOI: 10.5251/abjna.2011.2.4.652.660
|View full text |Cite
|
Sign up to set email alerts
|

Partial substitution of mineral nitrogen fertilizer by bio-fertilizer on (Anethum graveolens L.) plant

Abstract: A field experiment was conducted at the Experimental Farm of the Pharmaceutical Department, Agriculture college, Giza, Egypt to study the effect of partial substitution of mineral nitrogen fertilizer by biofertilizer and their effects on the growth, yield and chemical constituents of dill plant during the two successive seasons of 2007/2008 and 2008/2009. Because of the great importance of volatile oil, its composition was also investigated in this study. Five strains of bacteria (1-Azotobacter chroococcum, 2-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
26
0
7

Year Published

2012
2012
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(48 citation statements)
references
References 5 publications
10
26
0
7
Order By: Relevance
“…The best results were recorded with T1 in leaves and roots without bio-fertilizer were 52.41 and 73.66%, respectively. Finding results agree with those obtained by Hellal et al (2011) who showed that the utilization chemical N fertilizer alone or combined with bio-fertilizers treatments alone led to increasing yield and carbohydrates. Abdel-Gwad et al (2008) reported that the crude protein and ash of fodder beets were significantly increased by increasing nitrogen fertilizer level, while crude fibers and NFE take an opposite trend.…”
Section: The Effect Of Different Mineral N Fertilizer Rate and Spacinsupporting
confidence: 92%
“…The best results were recorded with T1 in leaves and roots without bio-fertilizer were 52.41 and 73.66%, respectively. Finding results agree with those obtained by Hellal et al (2011) who showed that the utilization chemical N fertilizer alone or combined with bio-fertilizers treatments alone led to increasing yield and carbohydrates. Abdel-Gwad et al (2008) reported that the crude protein and ash of fodder beets were significantly increased by increasing nitrogen fertilizer level, while crude fibers and NFE take an opposite trend.…”
Section: The Effect Of Different Mineral N Fertilizer Rate and Spacinsupporting
confidence: 92%
“…Application of inorganic with organic manure might have supplied the adequate and continuous amount of nutrient at different stages due to release of sufficient amount of nutrient by mineralization at a constant level that resulted in higher plant growth. The results are conformity with those reported by Selvarajan and Chezhiyan, (2001), Derzi et al, (2005) and Hellal et al, (2011).…”
Section: Effect Of Inm On Plant Heightsupporting
confidence: 83%
“…For the interaction, mineral fertilizer NPK in combination with different concentration of biofertilizer treatments (ADY) resulted the highest content of the total chlorophyll compared with the control in both seasons. Furthermore, the highest significant increase in the total chlorophyll content was obtained using 15.0 g / plant of NPK fertilizer plus bio-fertilizer at 6.0 g / l (ADY) as compared with the control.Such increase in photosynthetic pigments formation could be attributed to the role of yeast cytokinins delaying the aging of leaves by reducing the degradation of chlorophyll and enhancing the protein and RNA synthesis (Castelfranco and Beale 1983).These results were agreement with Hellal et al (2011) on dill plants.…”
Section: Iii-effect Of Npk and Active Dry Yeast Fertilizers On Chemicsupporting
confidence: 81%